Charles Jackson Train journals - Train, Charles Jackson, 1845-1906.
Photocopies of Train's journals documenting his latter years as a student at the United States Naval Academy, a European cruise (1864-1869), assignment at the U.S. Naval Observatory, and a cruise (1869-1870) aboard the U.S. frigate Sabine in the Mediterranean and to South America.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Sabine (Frigate); United States. -- Navy -- Cruise, 1864-1869.; United States. -- Navy -- Cruise, 1869-1870.; United States. -- Navy -- Foreign service -- Europe; United States. -- Navy -- Foreign service -- Mediterranean Region; United States. -- Navy -- History; United States. -- Navy -- Officers; United States. -- Navy -- Foreign service -- South America; United States Naval Academy; United States Naval Observatory; Midshipmen; United States -- History, Naval; Naval officers